Introduction to mixed-signal, embedded design - Doboli, Alex (Springer, 2011)
This textbook is written for junior/senior undergraduate and first-year graduate students in the electrical and computer engineering departments. Using PSoC mixed-signal array design, the authors define the characteristics of embedded design, embedded mixed-signal architectures, and top-down design. Optimized implementations of these designs are included to illustrate the theory. Exercises are provided at the end of each chapter for practice. Topics covered include the hardware and software used to implement analog and digital processing loops, various filter structures, amplifiers and other signal-conditioning circuits, analog to digital converters, pulse-width modulators, timers, and data structures for handling peripheral devices. The practical exercises contained in the companion laboratory manual, which was co-authored by Cypress Staff Applications Engineer Dave Van Ess, are also based on PSoC. PSoC's integrated microcontroller, highly configurable analog/digital peripherals, and a full set of development tools make it an ideal learning tool for developing mixed-signal embedded design skills.